A review of the fission programme at the CERN n_TOF facility - Tsinganis, A.; n_TOF Collaboration, for the (HNPS Advances in Nuclear Physics, 2019)
Since 2001, the scientific programme of the CERN n_TOF facility has focused mainly on the study of radiative neutron capture reactions, which are of great interest to nuclear astrophysics and on neutron-induced fission reactions, which are of relevance for nuclear technology, as well as essential for the development of theoretical models of fission. Taking advantage of the high instantaneous neutron flux and high energy resolution of the facility, as well as of high-performance detection and acquisition systems, accurate new measurements on several long-lived actinides, from 232Th to 245Cm, have been performed so far. Data on these isotopes are needed in order to improve the safety and efficiency of conventional reactors, as well as to develop new systems for nuclear energy production and treatment of nuclear waste, such as Generation IV reactors, Accelerator Driven Systems and reactors based on innovative fuel cycles. A review of the most important results on fission cross-sections and fragment properties obtained at n_TOF for a variety of isotopes is presented along with the perspectives arising from the newly added 19 m flight-path, which will expand the measurement capabilities to even more rare or short-lived isotopes, such as 230Th, 232U, 238Pu and 244Cm.